The Response of International Organizations to the Pathologies of the Political System in Kenya - Kruk, Aleksandra (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2024)
The article discusses some pathologies in Kenya which internal institutions of Kenya as well international institutions, such as the African Union, the East African Community, and Transparency International, are trying to overcome. After gaining independence in 1963, the presidency of Kenya was held by Jomo Kenyatta (1964–1978), Daniel arap Moi (1978–2002), Mwai Kibaki (2002–2013), Uhuru Kenyatta (2013–2022), and since 2022 it has been held by President William Ruto. These leaders have influenced the quality of governance but have not prevented the problems that Kenya faces. Despite the fact that Kenya’s leaders and society are judged from the perspective of meeting the standards of governance, the country still struggles with many pathologies. Artykuł omawia niektóre patologie w Kenii, które starają się przezwyciężyć wewnętrzne instytucje Kenii, a także międzynarodowe organizacje, takie jak Unia Afrykańska, Wspólnota Wschodnioafrykańska i Transparency International. Po uzyskaniu niepodległości w 1963 roku prezydencję w Kenii sprawowali Jomo Kenyatta (1964–1978), Daniel arap Moi (1978–2002), Mwai Kibaki (2002–2013), Uhuru Kenyatta (2013–2022), a od 2022 roku prezydentem jest William Ruto. Wskazani przywódcy mieli wpływ na jakość rządzenia, ale nie zapobiegli problemom, z jakimi boryka się Kenia. Pomimo że przywódcy i społeczeństwo Kenii są oceniani z perspektywy spełniania standardów sprawowania władzy, to państwo nadal boryka się z wieloma patologiami.
Odpowiedź międzynarodowych organizacji na patologie systemu politycznego w Kenii
Keywords: Kenya; corruption; equality; elections; political pathologies; Kenia; korupcja; równość; wybory; patologie polityczne